VD_FINDINFO HC / 2015 / 686 vom 9. Juli 2015 - VD Tribunal cantonal (2015)
DROIT DE GARDE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT, MINIMUM VITAL | 176 al. 1 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 176 CC